Israeli-Palestinian Conflict After Hamas Attacks October 7, 2023 (Framing Voa Indonesia and Deutsche Welle Indonesia) - Wesy Oktavina; Dhanurseto Hadiprashada; Dwi Aji Budiman (Publikasi Indonesia, 2024)
The conflict between Israel and Palestine for more than 7 decades until now has not ended. On October 7, 2023, the Israeli-Palestinian conflict came to a head again after Hamas broke into Israeli defenses. The Israeli military aggression on the Gaza Strip has had a tremendous impact, as it has claimed many lives and destroyed various facilities and infrastructure in Gaza. This research uses qualitative methods that are descriptive and use the constructivism paradigm. This study used the framing analysis model Zhongdang Pan & Gerald M. Konsicki. Based on the results of the study, there are similarities and differences in the news portals VoA Indonesia and Deutsche Welle Indonesia in reporting the Israeli-Palestinian conflict. In terms of news writing techniques, news portals VoA Indonesia and Deutsche Welle Indonesia have similarities. However, there is a difference, namely the VoA Indonesia news portal actually and intensively reports related to the Israeli-Palestinian conflict every day. Meanwhile, the Deutsche Welle Indonesia portal tends to be not actual and less news is published, because it is not published every day.